Strategi Pemberdayaan untuk Mengatasi Pengangguran di Kalangan Pemuda - Amniar Ati; Septianto Aldiansyah (Jurnal Penelitian Pendidikan Geografi, 2025)
The phenomenon of unemployment in rural areas reflects an imbalance between the availability of job opportunities and the growing workforce, which is further exacerbated by limited access to skills training. Matanauwe Village is one of the villages facing this issue, particularly among its youth. The purpose of this study is to identify the empowerment strategies implemented by the Matanauwe Village government in addressing youth unemployment. This research adopts a qualitative approach. The informants consist of 15 individuals, including the village head, community leaders, unemployed youth, and youth who are already employed or engaged in entrepreneurship. These informants were selected because they possess knowledge, experience, and direct involvement in unemployment issues and their solutions within the village. Data collection techniques used in this study include observation, in-depth interviews, and documentation. The data analysis techniques employed are data reduction, data presentation, and conclusion drawing. The findings of this study reveal that the empowerment strategies to overcome youth unemployment in Matanauwe Village include the provision of guidance or training, youth empowerment through farmer group initiatives, and youth empowerment through motorcycle repair and carpentry enterprises under the supervision of the Karang Taruna (youth organization). These strategies contribute to enhancing youth skills, independence, and employment opportunities, although the scope of these programs remains limited.